Akt/protein kinase B in skeletal muscle physiology and pathology - Wu, M.; Falasca, Marco; Blough, E. (2011)
The Akt/protein kinase B is critical regulator of cellular homeostasis with diminished Akt activity being associated with dysregulation of cellular metabolism and cell death while the regulation of Akt function has been well characterized in vitro, much less is known regarding the function of Akt in vivo. Here we examine how skeletal muscle Akt expression and enzymatic activity are controlled, the role of Akt in the regulation of skeletal muscle contraction, stress response glucose utilization, and protein metabolism, and the potential participation of this important molecule in skeletal muscle atrophy, aging, and cancer.